Iranian High School EFL Learners’ Attitude towards Online Learning during the Covid-19 Pandemic - Fatemeh Jalilinia (Journal of Languages and Language Teaching, 2021)
By the outbreak of the Covid-19 pandemic, students and teachers were pushed to adapt themselves to the online learning system. The current study is a quantitative attempt to investigate English as a foreign language students’ perception of online learning during the pandemic. For this purpose, 30 male and 30 female students at the high school level were chosen to answer a questionnaire in Iran, Tehran. The questionnaire used in this study is adopted from Rojabi (2020) and comprises two parts. The first half assesses the interaction among students and between students and the teacher whereas the second half measures students’ attitude towards their online learning platform. The data was interpreted through the SPSS software (version 24) and the results revealed that learners mainly have negative perspectives on online learning and would not suggest it for further educational years to come. The majority of participants struggled with having effective interaction. Also, most of them did not have pleasant experiences with the learning platform they were instructed to use. It is recommended that the current learning environment be improved and teachers apply strategies to involve students fully in the learning process throughout online sessions.